Integration of Formal Structure in Urban Centers - Rasheed, Khansaa Ghazi; Salman, Mohammed Kareem (Iraqi Journal of Architecture and Planning, 2018)
Today, our cities are witnessing rapid expansion, growth and transformation to meet needs, The most important of these transformations is the transform of parts of residential neighborhoods into urban centers dynamically with the growth and expansion of the city, And this made us stand on the problems experienced by these modern urban centers of the absence of the elements of a structured structure integrated with them as well as the factors that affect this came this research to highlight this important aspect of urban development and urbanization. The research deal with the definition of urban centers , patterns and the need for its establishment , to build a knowledge base that contributed to the diagnosis of the main problem of research (Lack of clarity on the problems of determining the structures of an integrated structure for urban centers) and to solve this problem this research requires a number of studies and hypotheses about the urban centers, And its structure and morphology, as well as the transformations that occur in the urban centers of these cites, its dimensions, aspect, and its reasons to reach the goal of research (Achieving a comprehensive theoretical framework on the transformations of urban centers and their structural structure). Thus, the basic hypothesis of research) Integrity of the formal structure of the urban center is realized by activating the center and re-organization of elements of the physical structure). The research adopted a descriptive analytical approach to discuss the research problem by taking Studies and suggestions on urban centers to extract basicMeanings and Build a comprehensive theoretical framework on the integration of the formal structure of urban centers. And application of the theoretical framework to the study area (Al-Mutanabi district).it was selected for the rapid pace of formal transformation and accelerated growth as a new urban center in the city of Baghdad. The research has concluded that the formal structure of the urban center is achieved by rearranging the elements of the physiognomy structure by achieving the concept of gradation of functional motifs This requires constant a controlled boundaries of urban center and a functional adaptive urban pattern .